MENDONGENG UNTUK MENUMBUHKAN LITERASI MEMBACA SISWA SDN 1 MAGUAN - Adzimatnur Muslihasari; Wafiyatu Maslahah; Wuli Oktiningrum; Rizka Fibria Nugrahani (FIP UNIRA MALANG, 2023)
Storytelling activities for students of SDN 1 Maguan aim to foster student reading leteraticy. The methods used include 3 stages, namely preparation stage; implementation stage; and evaluation stage. Preparations include observations and interviews about students' reading literacy levels and programs that have been implemented by the school, planning activity formats, and budgets. The observation show that SDN 1 Maguan has never been carried out storytelling activities and students' reading literacy tends to be low when viewed from the frequency of visits to the library. The community service program is carried out with one storyteller who utilizes fairy tale aids in the form of hand puppets. The participants are students of Maguan 1 elementary school grade 1 to 4 which totals 84 students. The organizing committee for this activity is PGSD UNIRA students. This activity is well carried out and proven to increase students' interest in reading which will lead to reading literacy. The recommendation that can be submitted to the school is to design an advanced program to increase the learning experience of students in order to improve students' reading literacy that can make it easier for students to enrich their vocabulary. So that easier to achieve reading literacy.